ANALISIS EFEKTIVITAS IKLAN TELEVISI KOPI INSTAN TOP COFFEE ENDORSER â€IWAN FALSâ€ - Setyawan, Iwan (Manajemen Bisnis, 2014)
This study aims to measure the effectiveness of television advertising endorser Top Coffee "Iwan Fals". The method used Direct Rating Method (DRM) and EPIC. Type of this study is a survey. The objects are students of universities in Malang. The data collection technique is non-probability sampling with convenience sampling technique. Direct Rating Method (DRM) and the EPIC methods are analytical tools to measure the effectiveness of television advertising endorser Top Coffee "Iwan Fals".  The result of Direct Rating Method indicates that ads endorser has a good category, and EPIC result shows that ads endorser is more effective. Based on the overall results from both analysis can be concluded that television advertising endorser Top Coffee "Iwan Fals" is good and effective. Keywords: Effectiveness, Direct Rating Method, Method EPIC